Kontribusi Daya Tahan Otot Tungkai dan Kecepatan Reaksi terhadap Passing Bawah Bolavoli Club Vonda Pekanbaru - Alvi Renanda; Raffly Henjilito (Journal on Education, 2023)
The purpose of this research was to determine the contribution of leg muscle endurance to volleyball forearm pass, the contribution of speed reaction to volleyball forearm pass, and the contribution of leg muscle endurance and speed reaction to volleyball forearm pass at Vonda Pekanbaru club. The design of this research was a quantitative correlational study with the total population was 12 athletes. To determine the sample, the researcher used total sampling technique where the entire population was sampled in this research. The instruments of this research that the researcher used were the leg muscle endurance test, the speed reaction test and the forearm passing test. With the following tests, the Wall Squad test is to determine the endurance of an athlete's quadriceps muscle strength, the Nelson hand reaction test which aims to measure hand reaction time with visual stimulation, and the forearm passing ability test to see how well a player is doing forearm passing. The data collection techniques in this research were in the form of observation, literature, tests and measurements. The correlation analysis technique was used the product moment correlation which is used to calculate the correlation from X1 (leg muscle endurance) to Y (forearm passing), the correlation from X2 (speed reaction) to Y (forearm passing), then the correlation from X1 (endurance leg muscles) and X2 (speed reaction) to Y (forearm passing). It can be concluded from this research that there was a contribution of leg muscle endurance to the forearm pass of the Vonda Pekanbaru club was 28.83%, the contribution of speed reaction to the forearm pass of the Vonda Pekanbaru club was 0.176%, and the contribution of leg muscle endurance and speed reaction to forearm passing of Vonda Pekanbaru club was 28.38%.